PRESERVING THE RUDAT TRADITION AS A MEANS OF ISLAMIC DA'WAH IN INDRAMAYU - Bambang Yuniarto; Muhamad Dawud, Kafitri, Wawang Euis Wasiat, Doni Hariyanto (Adisam Publisher, 2023)
The existence of rudat dance in West Java is almost extinct and not so popular along with the times and the impact of increasingly sophisticated technology and various modern games that are easily accessed by the millennial generation. Specifically in Indramayu Regency, rudat dance is still preserved by residents of Carik Block, Krasak Village RT.17 / RW.04 Jatibarang District through the Angling Dharma Rudat Dance Art studio actively, organised and continuously introduced to the surrounding community in various ways and da'wah which is acculturated with verses that display Islamic values. The purpose and objective of this writing is to find out the historicisation and meaning contained in the rudat dance seen from various sides. On the one hand as a means of da'wah, but on the other hand how the art of rudat dance to survive in the midst of the macrosociological currents of western culture which are not necessarily friendly to the norms and values of archipelago cultural life continues to uphold expensive assets and ancestral heritage as a mirror of the internalisation of the philosophy of traditional art with all its aesthetics. The methodology used in this research is descriptive qualitative. The data in the study was obtained through the process of interviews and observations, the data that has been obtained is analysed through four stages, namely data collection, data reduction, data presentation, and conclusion drawing.